HUBUNGAN FAKTOR PEMANFAATAN PROGRAM PROLANIS DI WILAYAH KERJA PUSKESMAS SUKAGUMIWANG TAHUN 2023 - Depi Yulyanti; Muhamad Fauzi; Siti Nurjani; Rudiansyah Rudiansyah (HOSPITAL MAJAPAHIT : JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO, 2024)
Diabetes mellitus can cause complications and become a public health problem which is the most important cause of death, morbidity and disability in the world. The prevalence rate of diabetes mellitus continues to increase in the 2013 Riskesdas, namely 6.9%, in 2018 it increased to 8.5%. In Indramayu itself, based on the profile of the Indramayu District Health Service in 2022, there are 17,868 diabetes mellitus sufferers.The aim of this research is to determine the factors associated with prolanis utilization programs.This research uses quantitative methods with a cross sectional approach. The population in this study was 9,332 people, the sample used the Slovin formula with a result of 99 respondents and the sampling technique used incidental sampling. The instrument used was a questionnaire. Using univariate and bivariate design analysis carried out with the Chi-Square Test. The factor that is related to the use of prolanis is support from health workers. It is hoped that the suggestions in this research will help health workers to socialize and motivate the public to take advantage of the prolanis program